Development of Constitutive Model for Precast Prestressed Concrete Segmental Columns. (27th March 2016) - Hafezolghorani Esfahani, M.; Hejazi, F.; Vaghei, R.; Nikbakht, E.; Tze, D. C. J.
Abstract : The interest of using precast segmental columns in construction of concrete bridges has significantly increased in recent years. One research area of concrete bridges is the application of Precast Prestressed Concrete Segmental (PPCS) Column in any structural analysis software or FE program code. Modeling a PPCS column, which consists of various materials with interaction between them, is complicated and time-consuming. This research attempts to formulate the stiffness matrix of PPCS columns in order to form the constitutive model in linear form to evaluate the response of the columns. A two-dimensional finite element model is presented in the finite element package ANSYS. Parametric studies are conducted by finite element models to verify the constitutive models for the PPCS column with a different number of concrete segments. Comparison between the constitutive model and the FE program results indicates that the constitutive model is accurate enough to predict the deformation of the PPCS columns.